Positive electrode sheet, secondary battery including same, and power device
Patent Information
- Application Number
- CN202410846404.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2044-06-26
AI Technical Summary
[0003]本申请针对干法导电剂分散困难的问题,提供了一种改善的干法正极片及含其的二次电池和用电装置
[0007]本申请的有益效果为:本申请的正极片中导电剂可以得到较好的分散,使得极片具有较低的体积电阻率和界面电阻率,同时能够实现高的倍率性能和快充性能。
Smart Images

Figure CN121215702B_ABST
Abstract
Description
Technical Field
[0001] This application relates to a positive electrode and a secondary battery and device including the positive electrode. Background Technology
[0002] Currently, electrode film processing technologies are divided into wet and dry processes. The wet process involves uniformly mixing active materials, binders, and conductive agents in a solvent to create a slurry mixture with a solid content of 40%-60%. This mixture is then coated onto a solid sheet current collector, and finally dried to evaporate the solvent and remove it from the electrode film. This process is energy-intensive, costly, and leaves solvent residue. The dry process involves mixing active materials, binders, and conductive agents, fiberizing them, and then forming the fiberized material into a dry electrode film. This dry electrode film is then composited with a solid current collector. This process has low energy consumption and a significant cost advantage. However, unlike the wet process, the dry process has limited dispersion capabilities, particularly for carbon black and carbon nanotubes. Furthermore, using large-particle carbon black or ultra-coarse carbon nanotube powder leads to low utilization of conductive carbon, resulting in low density of the conductive network and ultimately poor electrode conductivity, affecting the battery's rate performance and cycle performance. Summary of the Invention
[0003] This application addresses the problem of difficult dispersion of conductive agents in dry-process batteries by providing an improved dry-process positive electrode, a secondary battery containing the positive electrode, and an electrical device thereof. The conductive agent in this positive electrode can be better dispersed, and the electrode can achieve high rate performance and fast charging performance, while also having improved resistance, thereby enhancing cycle performance.
[0004] A first aspect of this application provides a positive electrode sheet, comprising a current collector and a dry electrode film located on the surface of the current collector. The dry electrode film comprises an active material, a binder, and a conductive agent. The active material comprises lithium iron phosphate, and the conductive agent comprises carbon black, carbon nanotubes, and graphene. The Z-value of the conductive agent satisfies the following condition: Among them, D SP The D50 particle size of the carbon black is expressed in μm. SP D is the primary particle size of the carbon black, in nm. CNT The D50 particle size of the aggregates of carbon nanotubes is expressed in μm. CNT D is the diameter of the carbon nanotube, in nm. GO The D50 particle size of the graphene is expressed in μm. GO D is the sheet diameter of the graphene, in μm; LFP is the D50 particle size of the lithium iron phosphate, in μm; a is the mass percentage of carbon black in the dry electrode film; b is the mass percentage of carbon nanotubes in the dry electrode film; c is the mass percentage of graphene in the dry electrode film.
[0005] A second aspect of this application provides a secondary battery comprising the positive electrode described in the first aspect.
[0006] A third aspect of this application provides an electrical device comprising the secondary battery described in the second aspect.
[0007] The beneficial effects of this application are: the conductive agent in the positive electrode sheet can be well dispersed, so that the electrode sheet has low volume resistivity and interface resistivity, while achieving high rate performance and fast charging performance. Detailed Implementation
[0008] For the sake of brevity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.
[0009] Unless otherwise stated, the terms used in this application have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).
[0010] The list of items connected by the terms "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0011] The term "dry electrode film" refers to an electrode film incorporating a binder matrix structure sufficient to support the film and maintain its shape, allowing the electrode film to operate independently without any external support elements, such as current collectors. For example, without other support elements, a dry electrode film can have sufficient strength to be rolled up, handled, and unrolled during the manufacturing process of a negative electrode sheet.
[0012] The dry electrode membrane in this application does not contain solvents. Here, "does not contain solvents" means that the dry electrode membrane does not contain detectable processing solvents, processing solvent residues, or processing solvent impurities. These processing solvents refer to the processing solvents used in the wet preparation of the positive electrode sheet, including but not limited to water, pyrrolidone, acetate, ketone, alcohol, diol, toluene, and xylene.
[0013] The present application will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0014] I. Positive Electrode
[0015] A first aspect of this application provides a positive electrode sheet, comprising a current collector and a dry electrode film located on the surface of the current collector. The dry electrode film comprises an active material, a binder, and a conductive agent. The active material comprises lithium iron phosphate, and the conductive agent comprises carbon black, carbon nanotubes, and graphene. The Z-value of the conductive agent satisfies the following condition: Among them, D SP The D50 particle size of the carbon black is expressed in μm. SP D is the primary particle size of the carbon black, in nm. CNT The D50 particle size of the aggregates of carbon nanotubes is expressed in μm. CNT D is the diameter of the carbon nanotube, in nm. GO The D50 particle size of the graphene is expressed in μm. GO D is the sheet diameter of the graphene, in μm; LFP is the D50 particle size of the lithium iron phosphate, in μm; a is the mass percentage of carbon black in the dry electrode film; b is the mass percentage of carbon nanotubes in the dry electrode film; c is the mass percentage of graphene in the dry electrode film.
[0016] In this application, the Z-value of the conductive agent represents its dispersion level and conductivity level. The inventors of this application have discovered that when a composite conductive agent of carbon black, carbon nanotubes, and graphene is used, and the conductive agent meets the above-mentioned Z-value conditions, the conductive agent can be well dispersed in the lithium iron phosphate cathode, giving the electrode a high conductivity level and low impedance characteristics, while also achieving high rate performance and fast charging performance.
[0017] Unless otherwise specified, D50 particle size in this application refers to Dv50 particle size. The D50 particle size in this application can be measured using conventional methods in the art, such as laser particle size analyzer. The testing method can be found in the national standard GB / T19077-2016 Particle Size Distribution Laser Diffraction Method.
[0018] In some embodiments, the Z value is exemplarily a range of 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, or any combination of these values. In some embodiments, 0.003 ≤ Z ≤ 0.030. If the Z value is too low, the conductive network formed by the conductive agent in the electrode is poor, resulting in high volume resistivity; if the Z value is too high, there is a problem with conductive agent dispersion during the dry electrode fabrication process, leading to large agglomerates of conductive agent in the resulting electrode.
[0019] In some implementations, 0.003 ≤ Z ≤ 0.012.
[0020] In this application, the D50 particle size of the carbon black is D SP This indicates the particle size of the secondary carbon black particles, which can be directly measured using a laser particle size analyzer. The primary particle size d of the carbon black. SP This indicates the diameter of the primary particles that make up the secondary carbon black particles. This particle size can be obtained by observation and statistical analysis using an electron microscope.
[0021] In some implementations, 0.3μm≤D SP ≤5μm. D SP Examples include 0.3μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 5μm, or a range of any two of these values.
[0022] In some implementations, 30nm≤d SP ≤80nm. d SP Examples include 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, or any combination of these values. If d SP If the size is too small, there will be difficulties in dispersion during the dry electrode fabrication process; if the size is too large, the network density in the electrode sheet will be low and the conductivity will be poor.
[0023] In this application, the D50 particle size of the carbon nanotube aggregates can also be obtained by laser particle size analyzer, representing the particle size of the carbon nanotube aggregates, not the particle size of a single carbon nanotube. The diameter d of the carbon nanotube... CNT It can be obtained by electron microscopy observation and statistics, and represents the diameter of a single carbon nanotube, not the diameter of a carbon nanotube aggregate.
[0024] In some implementations, 5μm≤D CNT ≤20μm. DCNT Examples include 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, or a range of any two of these values.
[0025] In some implementations, 10nm≤d CNT ≤50nm. d CNT Examples include 10nm, 12nm, 15nm, 18nm, 20nm, 22nm, 25nm, 28nm, 30nm, 32nm, 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, or a range of any two of these values. If d CNT If the size is too small, there will be difficulties in dispersion during the dry electrode fabrication process; if the size is too large, the network density in the electrode sheet will be low and the conductivity will be poor.
[0026] In this application, the D50 particle size of graphene can also be obtained by laser particle size analyzer. During laser particle size analyzer measurement, the graphene sample is equivalently simulated as a three-dimensional sphere. The graphene sheet diameter d... GO The size of the graphene sheet can be obtained by electron microscopy observation and statistical analysis.
[0027] In some implementations, 10μm≤D GO ≤40μm. D GO Examples include 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, or a range of any two of these values.
[0028] In some implementations, 5μm≤d GO ≤15μm. d GO Examples include 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or a range of any two of these values. If d GO If the size is too large, the network density in the electrode will be low, and the conductivity will be poor.
[0029] In some embodiments, the number of graphene layers is less than or equal to 5 layers, for example, 5 layers, 4 layers, 3 layers, 2 layers, or 1 layer.
[0030] In this application, the D50 particle size D of lithium iron phosphate is... LFP It can also be obtained by laser particle size analyzer. In some embodiments, 0.8 μm ≤ D LFP ≤1.5μm. D LFPExamples include 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, or any combination of these values.
[0031] In some implementations, 0.5% ≤ a ≤ 1.0%. a is exemplarily a range of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or any combination of these values.
[0032] In some implementations, 0.5% ≤ b ≤ 1.0%. b is exemplarily a range of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or any combination of these values.
[0033] In some implementations, 0.1% ≤ c ≤ 0.5%. c is exemplarily a range of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or any combination of these values.
[0034] In some implementations, 1.4% ≤ a+b+c ≤ 2.0%. If a+b+c is too low, the network density in the electrode is low, resulting in poor conductivity; if it is too high, the amount of main material used is reduced, thus lowering the energy density. In one implementation, a+b+c = 1.5%.
[0035] In some embodiments, the lithium iron phosphate content is 70 wt% or more, for example, 75 wt% or more, 80 wt% or more, 85 wt% or more, 90 wt% or more, 95 wt% or more, or 99 wt% or more, based on the total weight of the active material. In some embodiments, the active material also includes lithium manganese iron phosphate.
[0036] In some embodiments, the adhesive is selected from polytetrafluoroethylene, a mixture of polytetrafluoroethylene and polyvinylidene fluoride, or a mixture of polytetrafluoroethylene and polyvinylidene fluoride derivatives.
[0037] In some embodiments, the dry electrode film comprises 95.0% to 96.5% of the active material, 1.5% to 3.5% of the binder, and 1.4 wt% to 2% of the conductive agent.
[0038] In this application, the current collector is not specifically limited and can be any positive current collector disclosed in the prior art, including but not limited to aluminum foil and carbon-coated aluminum foil.
[0039] Secondary batteries
[0040] A second aspect of this application provides a secondary battery comprising the positive electrode described in the first aspect.
[0041] In some embodiments, the secondary battery is a lithium secondary battery. The lithium secondary battery includes, but is not limited to, lithium metal secondary batteries and lithium-ion secondary batteries.
[0042] In some embodiments, this application also provides a battery module. This battery module includes the aforementioned secondary battery. The battery module of this application uses the aforementioned secondary battery, and therefore has at least the same advantages as the aforementioned secondary battery. The battery module of this application can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0043] In some embodiments, this application also provides a battery pack including the aforementioned battery modules. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0044] III. Apparatus
[0045] A third aspect of this application provides an electrical device comprising at least one of the aforementioned secondary batteries, battery modules, or battery packs.
[0046] In some embodiments, the electrical device includes, but is not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems. To meet the device's requirements for high power and high energy density, battery packs or battery modules may be used.
[0047] In other embodiments, the power device may be a mobile phone, tablet computer, laptop computer, etc. This power device is typically required to be thin and light, and may use a rechargeable battery as its power source.
[0048] Example
[0049] Unless otherwise specified, all raw materials used in this application are commonly used in the field, and the methods in the embodiments are conventional methods in the field unless otherwise specified.
[0050] Test methods
[0051] 1. Determination of primary carbon black particle size, carbon nanotube (CNT) diameter, and graphene sheet diameter.
[0052] First, disperse the carbon black, CNT, or graphene sample and place it on a microgrid specifically designed for transmission electron microscopy (TEM) and store it properly. Second, observe the primary structure of the carbon black, the diameter of the CNT, or the diameter of the graphene sheet using TEM and obtain 5 effective field-of-view images. Finally, analyze all effective field-of-view images of the same carbon black, CNT, or graphene sample, measure and statistically analyze the dimensions of the primary structure of the carbon black, the diameter of the CNT, or the diameter of the graphene sheet, and take the average value.
[0053] 2. Determination of D50 of carbon black, CNTs, or graphene
[0054] The particle size distribution was measured using a laser diffraction particle size distribution measuring instrument (Mastersizer 3000) according to the particle size distribution laser diffraction method GB / T19077-2016. For volume distribution, the particle size at which the cumulative frequency starts from the smaller particle size side and reaches 50% is defined as D50.
[0055] 3. Determination of electrode volume resistivity
[0056] The middle strip of the prepared positive electrode sheet was rolled and pressed to a compaction density of 1.65 ± 0.05 g / cm³. 3 Four circular electrode sheets with a diameter of 14 mm were formed using a stamping machine, and the thickness of each electrode sheet was measured and recorded. The volume resistivity of the electrode sheets was tested using an RM2610 electrode resistance testing system. Three points were measured for each circular electrode sheet, and the average volume resistivity of the 12 points was taken.
[0057] 4. Measurement of electrode interfacial resistivity
[0058] The middle strip of the prepared positive electrode sheet was rolled and pressed to a compaction density of 1.65 ± 0.05 g / cm³. 3 Four circular electrode sheets with a diameter of 14 mm were formed using a stamping machine, and the thickness of each electrode sheet was measured and recorded. The interfacial resistivity of the electrode sheets was tested using an RM2610 electrode resistance testing system. Three points were measured for each circular electrode sheet, and the average value of the interfacial resistance at the 12 points was taken.
[0059] 5. Determination of 2C ratio retention
[0060] Using the positive electrode sheets prepared in the various embodiments and comparative examples as positive electrodes and the lithium metal sheet as the counter electrode (negative electrode), CR2016 coin cell half-cells were assembled in a glove box filled with Ar gas for rate performance testing. The separator of the coin cell half-cell was a Celgard 2400 polypropylene microporous membrane, and the electrolyte was a 1 mol / L lithium hexafluorophosphate (LiPF6) solution in a 1:1:1 volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).
[0061] During testing, the coin cell battery was charged at a constant current rate of 0.33C to 3.8V, then charged at a constant voltage rate until the current was less than 0.05C, and allowed to rest for 30 minutes. It was then discharged at a constant current rate of 0.1C to 2.0V, and allowed to rest for 30 minutes. The discharge capacity at the 0.1C rate was recorded. Subsequently, the battery was charged at a constant current rate of 0.33C to 3.8V, then charged at a constant voltage rate until the current was less than 0.05C, and allowed to rest for 30 minutes. It was then discharged at a constant current rate of 2C to 2.0V, and allowed to rest for 30 minutes. The discharge capacity at the 2C rate was recorded. The capacity retention rate of the battery at the 2C rate discharge = (2C rate discharge capacity / 0.1C rate discharge capacity) × 100%.
[0062] Example 1
[0063] Lithium iron phosphate (D50 1 μm), a binder, and a conductive agent were mixed to form an electrode mixture. The mass percentages of lithium iron phosphate, binder, and conductive agent in the electrode mixture were 96.0%, 2.5%, and 1.5%, respectively. Polytetrafluoroethylene (PTFE) was used as the binder. The composition and Z-value of the conductive agent are shown in Table 1. The number of graphene layers was less than or equal to 5. The resulting electrode mixture was sheared and fiberized, then rolled into a film on a roller mill to obtain a dry electrode film. The dry electrode film was then thermally laminated with carbon-coated aluminum foil to produce a dry-process positive electrode sheet. The single-sided active material loading of the resulting positive electrode sheet was 15 ± 0.3 mg / cm³. 2 .
[0064] Examples 2-10 and Comparative Examples 1-5
[0065] The dry-process positive electrode sheets of Examples 2-10 and Comparative Examples 1-5 are based on Example 1, but with adjustments to the Z-value of the conductive agent. Specifically, this is achieved by adjusting the mass percentage of carbon black, the primary particle size D50, the secondary particle size D50, or the mass percentage of carbon nanotubes (CNTs), their diameter, and the aggregate particle size D50, or the mass percentage of graphene, its sheet diameter, and the particle size D50. Except for the conductive agent, the dry-process positive electrode sheets of each example and comparative example are identical. Specific conductive agent adjustment measures and detailed data are shown in Table 1.
[0066] Table 1
[0067]
[0068]
[0069] Table 2 shows the coin cell performance data of the dry-process positive electrode sheets of each embodiment and comparative example. It can be seen that Embodiments 1-10 of this application have lower electrode volume resistivity and electrode interface resistivity, as well as higher 2C rate retention rate compared to Comparative Examples 1-5.
[0070] Table 2
[0071]
[0072] While some exemplary embodiments of this application have been described and illustrated, this application is not limited to the disclosed embodiments. Rather, those skilled in the art will recognize that modifications and changes may be made to the described embodiments without departing from the spirit and scope of this application as described in the appended claims.
Claims
1. A positive electrode, comprising a current collector and a dry electrode film located on the surface of the current collector, characterized in that, The dry electrode film comprises an active material, a binder, and a conductive agent. The active material includes lithium iron phosphate, and the conductive agent includes carbon black, carbon nanotubes, and graphene. The Z-value of the conductive agent satisfies the following condition: Among them, D SP The D50 particle size of the carbon black is expressed in μm. SP The original particle size of the carbon black is expressed in nm. D CNT The D50 particle size of the aggregates of carbon nanotubes is expressed in μm. CNT This is the diameter of the carbon nanotube, in nm; D GO The D50 particle size of the graphene is expressed in μm. GO This refers to the sheet diameter of the graphene, in μm. D LFP The D50 particle size of the lithium iron phosphate is expressed in μm. a is the mass percentage content of carbon black in the dry electrode film; b is the mass percentage of the carbon nanotubes in the dry electrode film; c is the mass percentage of graphene in the dry electrode film.
2. The positive electrode sheet according to claim 1, characterized in that, The Z-value of the conductive agent satisfies: 0.003 <Z<0.030。 3. The positive electrode sheet according to claim 1 or 2, characterized in that, The carbon black satisfies at least one of the following conditions: (i)0.3μm≤D SP ≤5μm; (ii)30nm≤d SP ≤80nm。 4. The positive electrode sheet according to claim 1 or 2, characterized by, The carbon nanotubes satisfy at least one of the following conditions: (iii)5μm≤D CNT ≤20μm; (iv) 10 nm < d < 50 nm CNT ≤ 50 nm.
5. The positive electrode sheet according to claim 1 or 2, characterized in that, The graphene satisfies at least one of the following conditions: (in)10μm≤D GO ≤40μm; (vi)5μm≤d GO ≤15μm; (vii) The number of graphene layers is less than or equal to 5.
6. The positive electrode sheet according to claim 1 or 2, characterized in that, The lithium iron phosphate satisfies: 0.8μm≤D LFP ≤1.5μm.
7. The positive electrode sheet according to claim 1 or 2, characterized in that, The positive electrode plate satisfies at least one of the following conditions: (viii) 0.5% ≤ a ≤ 1.0%; (ix) 0.5% ≤ b ≤ 1.0%; (x) 0.1% ≤ c ≤ 0.5%; (xi)1.4%≤a+b+c≤2.0%.
8. The positive electrode sheet according to claim 1 or 2, characterized by, The active material in the dry electrode membrane has a mass percentage content of 95.0% to 96.5%; and / or, The binder in the dry electrode film has a mass percentage content of 1.5% to 3.5%; and / or, The adhesive is selected from polytetrafluoroethylene, a mixture of polytetrafluoroethylene and polyvinylidene fluoride, or a mixture of polytetrafluoroethylene and polyvinylidene fluoride derivatives.
9. A secondary battery comprising a positive electrode as described in any one of claims 1-8.
10. An electrical device comprising the secondary battery of claim 9.
Citation Information
Patent Citations
Novel graphene lithium ion power battery positive electrode plate and preparation method therefor
CN107492665A
Lithium ion battery pole piece
CN110767875A